A preliminary study of sleep spindles across non-rapid eye movement sleep stages in children with autism spectrum disorder. Issue 1 (20th October 2022) - Kawahara, Midori; Kagitani-Shimono, Kuriko; Kato-Nishimura, Kumi; Ohki, Noboru; Tachibana, Masaya; Kato, Takafumi; Taniike, Masako; Mohri, Ikuko
Abstract: Study Objectives: Sleep spindles play a crucial role in multiple neuronal network functions. Initiation and termination of spindles are regulated by the thalamic reticular nucleus and thalamocortical network, and the spindle can be an index for brain organization. We conducted a preliminary study of the parameters of sleep spindles, focusing on sleep-stage temporal distribution in children with autism spectrum disorder (ASD) with normal intelligence/developmental quotients. Methods: We performed overnight polysomnography in 14 children with ASD (4–10 years) with normal full-scale intelligence quotient/developmental quotient (≥75) and 14 community samples (CS) of children. Sleep stages were scored according to the Rechtschaffen and Kales criteria. Spindle parameters were quantified and compared between these groups and the identified subgroups. Results: Sleep parameters did not differ between the ASD and CS groups, except for a higher rate of rapid eye movement (REM) sleep duration in ASD. Spindle parameters did not significantly differ between the groups, but spindle density was distributed in a broader range in the ASD group. Five children with ASD had a higher spindle density in stage 3 than in stage 2. The ratio of spindle density in stage 3 to that in stage 2 (stage 3/2 ratio) was significantly higher in ASD than in CS cases. Conclusions: The lower spindle density in stage 2 and relatively higher density in stage 3 in children with ASD may represent an abnormal generation of spindles due to insufficient maturation of the thalamic reticular nucleus and thalamocortical network.